Comparing the severity of knee Osteoarthritis and its outcomes in the veteran endurance runners and non-athletes - Mohammad Hosein Hamidi; Mohammad Samavati Sharif; Azar Aghayari (Sport Sciences and Health Research)
The purpose of this study was the comparison of severity of Knee Osteoarthritis and pain, movement difficulties and quality of life in the veteran endurance runners and non-athletes. 26 men were purposeful selected for this study and they was placed in the two groups (every group = 13 subjects). The recognition of injury with the conforming of clinical symptoms was done by a clinical orthopedic doctor through clinical diagnostic criteria of the American College of Radiology and clinical assessment was done by pain index and Lequesne's functional for knee osteoarthritis. Then, the world-known Knee injuries and Osteoarthritis Outcome Score (KOOS) questionnaire was used for the measurement of data collection. The independent t was used for the analysis of data (P < 0/05). There was no significant difference between the veteran endurance runners and non-athletes, despite of the higher mean of severity of knee osteoarthritis with 5/5% (P = 0/86), the severity of knee pain with 4/69% (P =0/40), the rate of difficulty in doing of daily activities with 3/52% (P =0/83), the rate of difficulty in doing of sport – recreational activities with 10/35% (P = 0/97) and the quality of life with 3/82% (P = 0/48) that it indicates the worse conditions in the veteran endurance runners than non-athletes. Therefore, we can concluded that running in championship level and endurance running does not increase dramatically the risk of knee osteoarthritis and problems related to it in the veteran endurance runners in the comparison of non-athletes.